The Saudi Government Reactions to YouTube based Programming: the Content Makers’ Perspective - Daoudi, Omar (AoIR Selected Papers of Internet Research, 2017)
The issue that this papers addresses is the political context of YouTube based programming in Saudi Arabia. YouTube based programmes empower the marginalized youth to engage actively with the public issues through creating video content by youth to youth; bypassing the traditional role of media gatekeepers in the country. This mode of social media activism is significant because it operates in a political, cultural and societal conservative system of Saudi Arabia. Importantly, the paper does not situate itself in the context of violence and riot as other studies investigate the role of social media during the Arab upheavals in 2011. Rather, it critically examines the role of social video in the political, economic and cultural context of Saudi Arabia and its dynamics process in a stable country. It adopts a qualitative approach of grounded theory in order to offer an in-depth and meaningful analysis for the social world, which cannot be achieved by incorporating digital positivism framework. The aim of this critical social media research is to explore the relationship between the authoritarian regime and the content creators who employ the cyberspace to reconstruct their digital public sphere. Two main categories are going to be investigated. First, the attitudes and the reaction of the state towards the YouTube based programming, which varied according to tone of the program. Secondly, it draws upon the experience of content makers to explore the adopted technique by some of the senior members of the Royal Family to contain YouTube based programmes.